THE EFFECT EMPOWERMENT OF COVID-19 LAYOFF THROUGH SELFEFFICACY ON THE LEVEL OF CRIME - Rima Rahmayanti; Wawan Hermawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The crime rate in Indonesia increased during the Covid-19 pandemic, crime statistics recorded by the Police, in the 19th and 20th weeks an increase of 7.04 percent. Meanwhile, narcotics cases have decreased significantly, namely between 1 and 57 percent. The public really feels the increase in criminal incidents during the corona pandemic. Robbers in minimarkets are on the rise, to the point of theft of motorbikes, mugging, milling around in the community. The presence of a number of layoff victim is one factor in increasing crime during a pandemic. Indonesian Ministry of Manpower In the face of the Covid-19 pandemic, explained that the Indonesian government in the labor sector had taken a number of actions or steps for its people. Namely, optimizing the implementation of the Pre-Employment Card Program, especially for workers who have been laid off by providing training and financial support; provide competency and productivity-based training incentives for affected communities; optimizing the role of the Work Training Center (BLK) through the Covid-19 Response BLK Program in order to mitigate the impact of the pandemic. In addition, the government has also carried out a massive program of development and expansion of job opportunities through labor and entrepreneurship for affected workers, prospective migrant workers, repatriated Indonesian migrant workers, and MSME workers; and other important approaches. This quantitative research aim to test effect the Ministry empowerment program through self efficacy to the Number of crime rate, 400 samples taken in Bandung city. Result show Ministry empowerment program and self efficacy from the victim of layoffs can reduce the crime rate during covid-19 pandemic in Bandung, Indonesia.